Investigating the Factors Affecting on Inflation with Emphasis on Knowledge-based Economy in Oil Exporting Countries - Hojjat Izadkhasti; Zarir Negintaji; Mohammad Mahdi Najafi (اقتصاد باثبات)
Inflation rate, one of the components of economic stability, has always been a special concern of policy makers. Therefore, in addition to increasing instability in the economy, a high inflation rate causes an increase in welfare losses, a decrease in household purchasing power, and an increase in uncertainty in the economy. In addition, it makes long-term decisions such as savings, investment, work, and retirement difficult, and by increasing the probability of making a mistake in estimating the future inflation rate, it causes losses to economic enterprises. Based on economic theories, factors affecting inflation are divided into three categories: inflation caused by demand pressure, inflation caused by cost pressure, and structural inflation. Therefore, inflation reduces the credibility of macroeconomic policymakers, especially the central bank, and its continuation can cause political and social instability. The components of the knowledge-based economy can also lead to the reduction of inflation through the channel of improving institutional quality, increasing the productivity of production factors, reducing production costs and improving the level of innovation. In this research, the factors affecting inflation with emphasis on the knowledge-based economy in oil exporting countries are investigated using the generalized moment method (GMM) in the time period (2011-2021). The results show that Lag of inflation, liquidity growth rate, GDP growth difference from liquidity growth, economy openness and government consumption expenditure in different scenarios have a positive effect and real GDP growth, institutional regime and economic incentives, human capital, research and market complexity have had a negative effect on the inflation rate. Information and communication technology index has not had significant effects on inflation.